Are Cleft Palate Fistulae a Cause of Dental Decay?. (May 2015) - Richards, Helen; Van Bommel, Annelotte; Clark, Victoria; Richard, Bruce
Aim: To investigate a possible correlation between fistula and dental decay in children at 5 years of age from a single-surgeon series of cleft palate repairs. Methods: Retrospective review of data over a 9-year period between 2003 and 2011 of cleft palate repairs performed by the senior author at Birmingham Children's Hospital, U.K. Data collected on age, sex, age at repair, presence of fistula, and number of decayed, missing, or filled primary teeth (i.e., decayed, missing, and filled teeth score) at age 5 years. Results: The overall fistula rate for this patient population was 24.1%. Fistulae were more common in the more severe forms of cleft type, as was frequency of dental decay. Comparison of fistula versus nonfistula groups showed a higher rate of dental decay (40%) in the fistula group, compared with only 20% in the nonfistula group ( P = .036). Conclusion: A positive association was established between dental decay and the presence of a fistula. Although not proven as causative, possible reasons for this include nasal mucus retaining sugary food in the mouth and an overall prolonged food-clearance time. The known association between severity of cleft and an increased likelihood of a fistula and severity of cleft and increased dental decay were again demonstrated but were not found to be the exclusive explanation for the new finding of an association between fistulae and higher dental decay rates.